HUBUNGAN KECERDASAN EMOSIONAL DAN KONSEP DIRI TERHADAP PENGUASAAN KETERAMPILAN TEKNIK DASAR PENCAK SILAT - Ervan Kastrena; Melsa Rahmawati; Asep Ramdan Afriyuandi (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2023)
ABSTRACT This study uses a quantitative descriptive method of correlational rxy with a population of 10 people who are pencak silat athletes at the Tapak Suci PIMDA 191 Cianjur. This research is motivated by the mastery of basic pencak silat technical skills which are the basis for athletes to master higher technical skills to compete. One of the factors is emotional intelligence and self-concept. Thus, this study aims to determine the relationship between emotional intelligence and self-concept on the mastery of basic pencak silat skills in pencak silat athletes at Tapak Suci PIMDA 191 Cianjur. The data was collected using a questionnaire technique for data on emotional intelligence and self-concept, and using the GPAI to test the basic skills of pencak silat. Data analysis used the SPSS version 20 application. The results of this study showed a significant relationship between emotional intelligence and self-concept on the mastery of basic pencak silat technical skills with the results of r arithmetic obtained 0.908 greater than r table 0.632. So it can be concluded from the results of this study that there is a significant relationship between emotional intelligence and self-concept on the mastery of basic skills of pencak silat. Keyword : Emotional intelligence, Self-concept, Basic skills of Pencak Silat